Effect of Water Diffusion on Adhesion Strength (Baghdad Science Journal, 2011)
The adhesion strength between Polyethylene (PE) film and Aluminum surface by using the adhesive material (Cyanoacrylate) has been studied. Aluminum (Al) was used as a substrate, and polyethylene (PE) was used as a film adhered to the Al surface. Standard specimens were prepared to use in the peeling test in dry condition, other specimens were immersed in water for 12 days at room temperature. the results for the specimens in the dry condition had shown that high value in the peel force and the peel energy, the peel force was 0.38*103 N/m and the peel energy was 0.605*103 N/m, peeling the film from Al surface leaves a residual of the adhesive material on both adherend, the failure for this specimen were combination of adhesive and cohesive failure. For the specimens that were immersed in water for 12 days, the results had shown that the effect of water on the specimen (Al /PE), where the water diffusion coefficient on the adhesive joint was 1.09*10-14 m2/s and the peel force was 0.062*103 N/m and the peel energy was 0.124*103 N/m, PE film was peeled from Al surface without any resistance.